Variabilidade genética e seleção de progênies de Eucalyptus Benthamii maiden et cambage - Costa, Rodolfo Manoel Lemes da [UNESP] (2014)
This work aimed to: ( a ) Study the genetic variability of Eucalyptus benthamii through genetic parameters for quantitative traits to develop strategies for breeding programs ; ( b ) Evaluate the genetic correlation between ages and between traits to determine the best parameter and age to select the superior individuals; and ( c ) Select the superior individuals by Multi - Effects Index. The genetic material used was 34 open pollination progenies of E . benthamii , arranged in three trials by randomized block design , varying the number of progenies, replications, and plants per plot , in Telemaco Borba municipality, PR , Brazil . The trails were measured by three, five , and seven years old for diameter at brea st height, plant height , and wood volume. The genetic parameters w ere estimate d by REML/BLUP procedure . There were significant di fferences (at 1% and 5% probability level ) between the progenies for all evaluated traits. The progenies have show n good performance when compared with literature. The values of coefficients of experimental variation and the coefficient of determination values of plot effects have show n low magnitude values , there was no high influence of the environment on the genetic parameters. The coefficients of g enetic v ariation showed there is genetic variability among progen ies , and then by selection is possible to obtain yield gains. Therefore, we concluded that there is ...